Modelling urban growth for Bangkok and assessing linkages with road density and socio-economic indicators - Lo, Edmond. Y. M. (2020)
The fastest urbanization is occurring in the Global South which includes many developing nations in Asia. However, a rapid and unplanned urban growth could threaten the sustainability of the process. A key step towards a sustainable urban development is to better understand interdependencies amongst urban growth patterns, infrastructure and socio-economic indicators. Here we chose Bangkok, Thailand as a megacity case study to assess the spatio-temporal urban growth dynamics and specifically its dependency with road density at intra-city scales. The SLEUTH urban growth model is further applied for predicting future expansion over the next decade and to assess the future intra-city expansion. Urban expansion patterns for Bangkok were generated for 1987 and 2017 using Landsat derived urban land-cover maps. Open Street Map (OSM) is used to generate a 2017 road density map. The urban expansion (1987-2017) was observed to follow a radially outward expanding pattern inland, with the logarithmic urban expansion rate having an inverted concave trend with road density. The rising/falling limbs then indicated an increase/decrease of urban expansion for which a road density “turning point” is readily identified and further used to develop a road density-based zoning map that highlights the different intra-city urban expansion rates. The SLEUTH predicted urban growth till year 2027 which also showed expansion outward from existing urban areas. The future expansion trend is also consistent with the turning point trend. This study showed that such spatial-temporal analysis of urban expansion coupled with SLEUTH can be useful for investigating likely outcomes of city development plans.